Factorial invariance of the moral character of Muslim personality scale: confirmatorv factor analvsis of Yemeni and Malaysian teachers - K, Al-Ammar, fawziah; Ahmed Mohamed, Ismaiel Hassanein; Nordin, Mohamad Sahari; Ismail, Khamsiah (2013)
The study armed to assess evidence of measurement equivalence of Moral Character of Muslim Personality (MCMP). Teachers from two targeted countries were called to participate in answering two versions of the instrument: Arabic version of MCMP used to collect data from Yemeni teachers (n=321) and Malaysian teachers (n=213) answered on Bahasa Malaysia version of the MCMP. Precisely, the study examines the factorial invariance of teh MCMP on the data collected from two samples. Multi-group of Confirmatory Factor Analysis (MGCFA) used to examine data across two samples, using the software of SEM technique (AMOS). The results of multi-group of CFA support of the configural invariance (second-order)for the hypothesized MCMP model. The results of CFA show that factors of cooperation, striving with wealth and self, reconciliation voluntary charity, truth, fulfilling promises, forgivingness, and steadfastness are applicable in two cultures based on data collected from different samples. The goodness-of fit statistics related to constrained two-groups for the hypothesized model of MCMP show good-fit indices, supporting validity of the MCMP model across two samples. The value of Chi-square was insignificant (p=0.001), Root Mean Square Error Apprecioation (RMSEA) =04, Comparative Fit Index (CFI) = 0.92, and Incremental Fir Index (IFI)=0.92. The findings suggest many implications for educators and policy makers in two countries to recruit teachers who exemplify good Islamic moral.